2014
DOI: 10.1093/heapro/dau011
|View full text |Cite
|
Sign up to set email alerts
|

Canadian adolescents' perspectives of cancer risk: a qualitative study: Table 1:

Abstract: Research examining adolescents' understandings of cancer and cancer risk is limited. Accordingly, we conducted an ethnographic study that sought to extend our limited understanding of Canadian adolescents' perspectives of cancer and cancer prevention including how adolescents conceptualize and understand cancer risk. This article addresses findings specific to adolescents' perspectives of cancer risk. Seventy-five adolescents (11–19 years old) took part in the study. Two individual open-ended interviews were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…HCPs. This extends to everyday decision-making by teens not living with FIA (Woodgate, Safipour, & Tailor, 2015) and points to the need for all parties to recognize the value and competence of teens who manage living with FIA daily. From the studies reviewed, teens desire guidance and support, yet those in authority tend not to listen to their needs or accept teens as experts in living with FIA.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…HCPs. This extends to everyday decision-making by teens not living with FIA (Woodgate, Safipour, & Tailor, 2015) and points to the need for all parties to recognize the value and competence of teens who manage living with FIA daily. From the studies reviewed, teens desire guidance and support, yet those in authority tend not to listen to their needs or accept teens as experts in living with FIA.…”
Section: Discussionmentioning
confidence: 88%
“…Studies of teens living with chronic illness describe teens as aware of potential poor outcomes, but weigh other factors relating to how they must live with chronic illness differently than their parents or HCPs. This extends to everyday decision‐making by teens not living with FIA (Woodgate, Safipour, & Tailor, ) and points to the need for all parties to recognize the value and competence of teens who manage living with FIA daily. From the studies reviewed, teens desire guidance and support, yet those in authority tend not to listen to their needs or accept teens as experts in living with FIA.…”
Section: Discussionmentioning
confidence: 95%
“…Researchers must generate meaningful evidence concerning policy acceptability and impacts (and consequences) of implementation. Knowledge brokers, and government relations and advocacy practitioners, must effectively communicate that evidence to those with broad scale policy influence [46]. Further, this finding suggests that it may be worthwhile to work closely with supportive stakeholders tied to communities (e.g., schools, workplaces, and media) on issues with less support; here, advocacy efforts can generate political allies, networks, and momentum in favor of environment-level policies [38].…”
Section: Discussionmentioning
confidence: 99%
“…Across the studies overall, Diepeveen et al [41] found that attitudes varied across risk factors (as previously noted), with the intrusiveness of the intervention (less intrusive interventions garnering more support), with the stage of implementation (interventions becoming more acceptable over time), and with the target of the intervention (children and businesses being more acceptable than individual adults). Niederdeppe et al [35] and others have investigated the nature of ideological beliefs underpinning these attitudes, demonstrating that framing cancer prevention as a societal versus individual responsibility affects positive or negative attitudes toward healthy public policy in various arenas [27,34,35,[43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1995, when the study by Oakley et al 27 was conducted, progress has been made in cancer prevention with healthy youth changing their perspectives of cancer risk factors. 30 Advancement in research has resulted in more breakthroughs in cancer treatment outcomes and more suggestions have been made at moving away from describing cancer using military metaphors because they can have detrimental effects on cancer prevention and experiences of people with cancer. 15 31 32 To arrive at healthy adolescents’ description, qualitative research is needed that will afford them the opportunity to describe cancer in ways that are significant to them.…”
Section: Introductionmentioning
confidence: 99%